Effect of Piper betle L. extract on growth of Colletotrichum capsici, causal agent of anthracnose of chili - Zahari, Nur Asifa (2016)
Chili is one of the most important crops grown worldwide. It ranks as the most popular fruit vegetable and occupies the highest hectarage among the fruit vegetables in Malaysia. However, like any other crops of economic importance, chili production is restricted by various pests and diseases. Anthracnose disease is one of the major economic constraints to chili production worldwide, especially in tropical and subtropical regions. Synthetic fungicides has been used traditionally to control the postharvest diseases, but their excessive use complemented with high costs, residues in plants, and development of resistance, has left a negative effect on human health and the environment. The increasing demand of consumers towards chemical free produce and their concern for health and environmental pollution have develop the interest toward other alternatives. Naturally occuring biologically active compounds from plants are generally assumed to be safer and less hazardous then the synthetic compounds. In view of this, this research is conducted to determine the possibility of using extract from betel leaves to control or inhibit the pathogen causing postharvest disease on chili (Capsicum annuum L.). The water and ethanol extracts showed varying degree of inhibitory on Colletotrichum capsici growth, with the ethanol extracts being more effective. Mycelial growth of C. capsici was significantly (P<0.05) reduced by 50% ethanol extracts of P. betle. Spore production was also significantly (P<0.05) reduced by 50% ethanol extract of P. betle ( 0.00 x 104 spore/ml). Spore germination reduced by 50% ethanol extract of P. betle (0.00%). These results show that higher concentration of the ethanol extract are more effective for the suppression of C. capsici growth and spore production.